WAIS Divide WDC06A Discrete ICP-MS Chemistry - Kreutz, Karl (IEDA: US Antarctic Program Data Center, 2017)
Abstract: This dataset includes discrete ICP-MS chemistry data generated at the University of Maine for the top 577 m of the WAIS Divide deep ice core (WDC06A). There are two parallel datasets, produced from a single set of samples that were melted continuously, collected by fraction collector and split manually (by pouring). The first set was acidified to 10% v/v nitric acid and allowed to leach for one month prior to analysis. These are referred to as "total" samples (see below). The second set were filtered using individual hand-held 0.45 um filters and syringes, then acidified to 10% v/v nitric acid and analyzed. These are referred to as "dissolved" samples. Reported depths are based on values assigned during melting; please note that these are subject to change. Please contact Karl and Bess if you plan to use the data or have any questions.